Pengembangan Sistem Informasi Kepegawaian Berbasis Web Pada PT. NNA - Saputra, Toni; Kesuma, Dorie P (Universitas Multi Data Palembang, 2025)
PT NNA is a company engaged in construction in Palembang City. Currently, the staffing system owned by the company is still done simply, namely filing employee data manually and filing has not been done in a system. This causes the company to experience difficulties in finding employee data and takes a long time in making staffing reports. The staffing system is a system developed to facilitate companies in searching and using employee data. The purpose of developing a staffing system is employee data, recruitment, leave, mutation, demotion, reward, punishment, promotion, assignment, resignation, and dismissal. The staffing system designed is website-based to facilitate its use. The method used in system development is RUP (Rational Unifed Process) and uses the PHP programming language and MySQL database. The results of the system testing table that has been developed can function properly and successfully, and the system can be accepted by the company.